Chloroquine Ingestion to Prevent SARS-CoV-2 Infection: A Report of Two Cases - Graff, Jonathan (Clin Pract Cases Emerg Med, 2021)
INTRODUCTION: Amid the global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), chloroquine and hydroxychloroquine were being studied as agents to prevent and treat coronavirus disease 2019. Information about these agents and their effects circulated throughout the general public media, raising the concern for self-directed consumption of both pharmaceutical and non-pharmaceutical products. CASE REPORT: We present two cases of chloroquine toxicity that occurred after ingestion of an aquarium disinfectant that contained chloroquine phosphate in a misguided attempt to prevent infection by SARS-CoV-2. One patient had repeated emesis and survived, while the other was unable to vomit, despite attempts, and suffered fatal cardiac dysrhythmias. CONCLUSION: These cases illustrate the spectrum of toxicity, varied presentations, and importance of early recognition and management of chloroquine poisoning. In addition, we can see the importance of sound medical guidance in an era of social confusion compounded by the extremes of public and social media.